NAD+‐aminoaldehyde dehydrogenase candidates for 4‐aminobutyrate (GABA) and β‐alanine production during terminal oxidation of polyamines in apple fruit. Issue 19 (18th August 2015) - Zarei, Adel; Trobacher, Christopher P.; Shelp, Barry J.
Abstract : The last step of polyamine catabolism involves the oxidation of 3‐aminopropanal or 4‐aminobutanal via aminoaldehyde dehydrogenase. In this study, two apple ( Malus x domestica ) AMADH genes were selected ( MdAMADH1 and MdAMADH2 ) as candidates for encoding 4‐aminobutanal dehydrogenase activity. Maximal activity and catalytic efficiency were obtained with NAD + and 3‐aminopropanal, followed by 4‐aminobutanal, at pH 9.8. NAD + reduction was accompanied by the production of GABA and β‐alanine, respectively, when 4‐aminobutanal and 3‐aminopropanal were utilized as substrates. Md AMADH2 was peroxisomal and Md AMADH1 cytosolic. These findings shed light on the potential role of apple AMADHs in 4‐aminobutyrate and β‐alanine production. Abstract : Recombinant Md AMADHs utilized 3‐aminopropanal and 4‐aminobutanal. Md AMADH2 was peroxisomal whereas Md AMADH1 was cytosolic. A role for Md AMADHs in polyamine oxidation in apple fruit is proposed.